Outcomes of Sinonasal Squamous Cell Carcinoma with and without Association of Inverted Papilloma: A Multi-Institutional Analysis. Issue 5 (September 2017) - Lobo, Brian C.; D'Anza, Brian; Farlow, Janice L.; Tang, Dennis; Woodard, Troy D.; Ting, Jonathan Y.; Sindwani, Raj
Introduction: Sinonasal squamous cell carcinoma (SCC) accounts for <1% of all malignancies but represents 70% of sinonasal cancer. Up to 10% of SCCs are associated with inverted papilloma (IPSCC). Studies that compare patients, treatment, and outcomes of SCC and IPSCC are absent in the literature. Methods: A retrospective review of patients with SCC and those with IPSCC at Cleveland Clinic and Indiana University from 1995 to 2015. The records were analyzed for demographics, tumor characteristics, treatment, and outcomes. Results: The study comprised 117 patients with SCC, of whom, 29 had IPSCC. The mean age at diagnosis was similar: 63 and 64 years for patients with SCC and patients with IPSCC, respectively; with female patients representing 36% and 34%, respectively (p > 0.99). Smokers represented 64% of the patients with SCC and 55% of patients with IPSCC (p = 0.3); excessive alcohol intake was noted in 16% of the patients with SCC and 21% of the patients with IPSCC (p = 0.56). The maxillary sinus was most commonly involved, followed by the nasal cavity (51% versus 35% SCC, 45% versus 38% IPSCC). Frontal ethmoid and sphenoid sinuses contained primary tumors only in patients with SCC. Upfront treatment was surgery in 84% of patients with SCC and 97% of patients with IPSCC (p = 0.18); 68 and 55% received radiation, respectively, and 25 and 21% received chemotherapy, respectively. Overall survival averaged 5.5 and 3.4 years for patients with SCC and patients with IPSCC, respectively (p = 0.12); disease-free survival was 4.8 and 2.9 years, respectively (p = 0.18). Nodal metastasis was more likely in patients with SCC (18 versus 0%; p = 0.02). When divided into high- and low-stage disease: more common nodal metastases were demonstrated in high-stage SCC than in low-stage disease (p = 0.03). Overall survival was decreased between high- and low-grade disease but not when subdivided between SCC and IPSCC. Conclusion: Although SCC with and without IP association are considered different diseases, their demographics and outcomes seem similar. Nodal metastasis was noted to be higher in the SCC cohort, which may indicate different tumor biology. Further study is warranted.